The incidence of subsidies to residential public services in Argentina: The subsidy system in 2014 and some alternatives - Christoph Lakner; Maria Ana Lugo; Jorge Puig; Leandro Salinardi; Martha Viveros (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2016)
More than a decade of energy and transport subsidies have weakened Argentina's fiscal capacity. Following the 2001 crisis, public services tariffs were frozen in an attempt to offset the negative effects on households' real purchasing power. However, these subsidies steadily increased over the years, particularly since 2006, becoming a significant fiscal burden. Though subsidies can be a tool to protect the poor, in Argentina they led to distortions and a large share have been absorbed by upper classes and non-residential consumers. This paper first analyzes the incidence of the 2014 system of residential federal subsidies to residential public services (defined as electricity, gas, water and transport) and then simulates the distributional impacts of alternative subsidy structures. Simulations on the electricity sector suggest that targeting consumption levels through a simple lifeline tariff is not sufficient to achieve a propoor incidence of subsidies. Instead, explicit targeting is necessary (though not sufficient) and needs to ensure comprehensive coverage of the poorest households. Similarly, on the transport sector show that the existing tariffs are not well-targeted, but that an expanded set of social programs could improve coverage of the poorest. Gas subsidy simulations showed that a social tariff would virtually eliminate the subsidy, suggesting that there is little overlap between the receipt of social programs and access to piped gas.
Keywords: 330